PD-L1 expression and characterization of its carrier macrophages in placentas with acute and specifically post-SARS-CoV-2 infection - Seefried, Marina; Mittelberger, Johanna; Franitza, Manuela; Garrido, Fabian; Wild, Carl Mathis; Ditsch, Nina; Protsepko, Oleksii; Kuhn, Christina; Dannecker, Christian; Altevogt, Peter; Jeschke, Udo; Sammar, Marei (Histochemistry and cell biology, 2024)
At the beginning of the coronavirus disease 2019 (COVID-19) pandemic, uncertainties about the virus and its dangers during pregnancy caused great uncertainty and fear, especially among pregnant women. New data suggest an increased risk of obstetric complications, including maternal complications, preterm labor, intrauterine growth restriction, hypertensive disorders, stillbirths, gestational diabetes and risk, of neonatal developmental disorders. In addition, preeclampsia (PE)-like syndromes were also induced by severe COVID-19 infection. Therefore, the aim of this study was to investigate the expression of CD68 and CD163 and PD-L1 on placental tissues from acute covid patients, patients who survived a covid-19 infection and normal term controls that are known to be dysregulated in preeclampsia cases. We examined a total of 60 placentas from women that had given birth to female or male offspring in the University Hospital Augsburg. We investigated ten acute COVID-19 females, ten acute COVID-19 males, ten post-COVID-19 females, ten post-COVID-19 males, ten female term controls, and ten male term controls. Immunohistochemical staining against CD68, CD163, and PD-L1 was performed and the expression of the markers was evaluated with an immunoreactive score (percentage score). Identity of CD163- or PD-L1 expressing cells was analyzed by double immune fluorescence analyses. In opposite to PE, CD163 positive maternal macrophages are significantly upregulated in the decidua of male acute COVID-19 placentas. PD-L1 is significantly upregulated on male acute- and post-COVID-19 decidual immune cells and on male post-COVID-19 extravillous trophoblast cells. Surprisingly the observed effects are related to the fetal gender as they were not observed in female offsprings. Further investigation is necessary to analyze especially the imprinting effect of this infection.
Gesehen am 27.06.2025